Konselor Dalam Bimbingan Dan Konseling Kelompok Dengan Expressive Arts Therapy - Putriani, Lisa (BKI IAIN Pontianak, 2021)
Abstract:The phenomenon at school is that there are students who during the counseling process do not convey what their anxiety, fears and fears are. This may be due to the psychological impact of various life experiences, such as trauma due to bullying by classmates on social media. If this psychological impact is allowed to drag on, it will become a complex problem for students. One of the services that counselors can provide by activating group dynamics is group guidance and counseling services with expressive arts therapy. Through an expressive art therapy approach, clients can communicate and express their feelings and thoughts through activities related to art, music, dance, drama, poetry, games. In group counseling with an expressive art therapy approach, the most important thing is that the group is able to develop the ability to express and communicate authentically and what is in themselves and what is the burden on their minds, as well as those who are the object of their anxiety through various approaches that counselors can use with expressive tools. therapy. This article will discuss the role of counselors in group guidance and counseling using the literature study method. Can be used as an alternative used by school counselors to help group members to meet emotional needs, build self-acceptance, increase self-esteem, reduce anxiety, address cognitive needs, and develop social skills in groups.